Annual Plan 1988-89 - Planning Commission (Planning Commission, 1988)
The Annual Plan for 1988-89 which is the fourth year of the Seventh Five Year Plan has been formulated in the light of the objectives, policies and programmes thrust indicated in the Seventh Five Year Plan and the performance of the economy in 1987-88 .which witnessed one of the severest droughts of the century. While seeking to promote balanced growth, it lays emphasis on implementation of area specific and beneficiary oriented anti-poverty programmes in order to generate additional employment and incomes for the weaker sections of the society.
Government of India Planning Commission
Government of India Planning Commission